African Easterly Wave Dynamics in Convection‐Permitting Simulations: Rotational Stratiform Instability as a Conceptual Model - James O. H. Russell; Anantha Aiyyer; J. Dylan White (Journal of Advances in Modeling Earth Systems, 2020)
Abstract We examine the upscale effect of moist convection on African easterly waves (AEWs) by limiting condensational heating and initial ambient moisture in convection‐permitting simulations. Moist convection is fundamental in maintaining and destabilizing AEWs. The contribution from barotropic‐baroclinic instability, albeit important, is relatively smaller. Mesoscale convective systems (MCSs) are initiated downstream of the AEW troughs and are associated with extensive trailing stratiform cloud regions. Using a potential vorticity (PV) budget, we show that the attendant diabatic heating profile reinforces the AEW. A model for destabilization is proposed that relies on the phasing of stratiform heating and the PV anomaly of the AEW. It qualitatively resembles stratiform instability and stretched building blocks hypotheses introduced in previous studies. The generation of PV by deep moist convection in the vicinity of the trough counters the shearing effect of the background flow. This helps maintain an upright PV column, which is conducive for formation of tropical cyclones. AEW propagation is dominated by advective processes and intermittently modified by moist convection when large MCSs move ahead of the AEW.